Comparison of 2D and 3D sequence models for archery shooting analysis using vision-based pose estimation and kinematic features - Park, J. (Journal of Asian Society for Health & Exercise, 2025)
PURPOSE : This study aimed to compare the performance and efficiency of sequence models — LSTM and GRU — using both 2D and 3D motion data for classifying archery shooting techniques. The goal was to evaluate how data dimensionality and model architecture influence classification accuracy, computational cost, and practical applicability in sports motion analysis.